Religious Leadership and Political Triumph: A Case Study of Kiai and Santri Strategies in the 2018 Pamekasan Local Elections - Abd Rohman (Jurnal Mengkaji Indonesia, 2023)
Abstract: This research examines the Kiai Pondok Strategy employed by an Islamic boarding school and its students (known as Santri) in successfully supporting a candidate for the position of Regent and Deputy Regent in the 2018 Regional Election in Pamekasan. Studying this subject is crucial due to the prevailing influence of terms such as "Bhuppa 'Bhabhu,' Ghuru, Ratho" in the public discourse of Madura. The figure of Kiai, particularly in the Regency of Pamekasan, Madura, plays a significant role in driving societal transformation, particularly in politics. Purpose: This research seeks to determine the roles of Kiai and Santri in the electoral contestation in the Pamekasan Regency. Design/Methodology/Approach: This research employs a qualitative methodology scientifically designed to uncover the meaning or understanding of a phenomenon and provide information about it.  Information was acquired via comprehensive interviews. The data analysis encompassed data reduction, data presentation, drawing conclusions, and verifying the data. The study was conducted using detailed, comprehensive, and easily comprehensible phrases. Findings: The research findings demonstrate that the mapping support for Kiai in each location of Regency Pamekasan varies. However, there is a higher level of support towards two prominent figures, notably Ra-Badrut and Raja'e. Subsequently, within the Kiai's strategic approach framework, Islamic boarding schools and their Santri actively seek societal support. They undertake initiatives to garner backing from the community, such as arranging for the transportation of students back to their homes and disseminating their teachings through lectures and social media platforms. Subsequently, the student method disseminates to society, garnering support from individuals eager to learn and endorse Kiai's teachings, whether Ustadz or Santri. The partnership consisting of Ra-Badrut and Raja'e emerged as the winners in the 2018 Pamekasan district head election. Originality/value: Indeed, research has been conducted on the role of kiai in political contestation. However, this research specifically targets the Pamekasan Regency area, which no one has investigated. Hence, this study is limited to the geographical scope of Pamekasan Regency. Additionally, the political sway of Kiai in Pamekasan Regency is remarkably potent, making it a compelling subject for further research.